KONTROL INFEKSI DALAM KEDOKTERAN GIGI: PENATALAKSANAAN POKET PERIODONTAL DENGAN TERAPI OKSIGEN (INFECTION CONTROL IN DENTISTRY: MANAGEMENT OF PERIODONTAL POCKET WITH OXYGEN THERAPY) - Dewi Nurul M; Devie Falinda (Fakultas Kedokteran Gigi Universitas Jember, 2010)
Periodontal disease is a chronic inflammatory disease and has a potency to be a focal infection which can spread the bacteria intra- and inter-individually. Subgingival biofilm anaerobic bacteria is the main causative factor of this disease. To change the anaerobic to aerobic environment is among several methods to control thecross infection during the periodontal treatment. This method is clinically available and will be describe in this paper.